How COVID-19 Affects Lung Transplantation: A Comprehensive Review - Vachtenheim, Jiri; Novysedlak, Rene; Svorcova, Monika; Lischke, Robert; Strizova, Zuzana (Journal of clinical medicine, 2022)
Lung transplant (LuTx) recipients are at a higher risk of developing serious illnesses from COVID-19, and thus, we have closely reviewed the consequences of the COVID-19 pandemic on lung transplantation. In most transplant centers, the overall LuTx activity significantly declined and led to a specific period of restricting lung transplantation to urgent cases. Moreover, several transplant centers reported difficulties due to the shortage of ICU capacities. The fear of donor-derived transmission generated extensive screening programs. Nevertheless, reasonable concerns about the unnecessary losses of viable organs were also raised. The overall donor shortage resulted in increased waiting-list mortality, and COVID-19-associated ARDS became an indication of lung transplantation. The impact of specific immunosuppressive agents on the severity of COVID-19 varied. Corticosteroid discontinuation was not found to be beneficial for LuTx patients. Tacrolimus concentrations were reported to increase during the SARS-CoV-2 infection, and in combination with remdesivir, tacrolimus may clinically impact renal functions. Monoclonal antibodies were shown to reduce the risk of hospitalization in SOT recipients. However, understanding the pharmacological interactions between the anti-COVID-19 drugs and the immunosuppressive drugs requires further research.
Keywords: treatment; COVID-19; immunosuppression; transplant activity; lung transplantation